Ross Postmistress Mrs. Ellen M. Nelson, 1896 (Roseau County Historical Society, 121 Center Street East, Suite 101, Roseau, MN 56571; http://www.roseaucohistoricalsociety.org, 1896)
dc56b32289c0215f57ef2c643d4bc1e0
Portrait of Mrs. Ellen M. Nelson postmaster of Ross. Photographs marks say she is the sister of Mrs. Wm. Warner, daughter of Yankee Nelson. 1896
United States
Minnesota
Roseau
Main town
Dieter Township; Ross
Roseau River
Keywords: Post Office; Portrait; Women; Women; Clothing and dress; Hairstyles; Portrait photographs; Business and industry; Communication